T-cell sensitisation to hepatitis B virus surface antigens - Paul, S; Tabassum, S; Islam, MN (Mymensingh Medical Journal, 2007)
Mymensingh Med J. 2006 Jan;15(1):66-70 The abstract of this article is available on the PubMed website